Tolerance of Earthworms (Eudrilus eugeniae) to 2,4-D Dimethyl Amine Herbicide - Suhandoyo; Aji, Gesang Putranto Dwi (Indonesian Journal of Bioscience (IJOBI), 2024)
The purpose of this study was to determine (1) the tolerance of earthworms (Eudrilus eugeniae) to the herbicide 2,4-D dimethyl amine, and (2) the response of increased biomass, behavior, and morphology of earthworms (Eudrilus eugeniae) when exposed to subletal doses of the herbicide 2,4-D dimethyl amine. This research is an experimental research conducted in two stages of research. The first stage to look at herbicide toxicity, includes LD50, upper threshold, and lower threshold. The second stage is a follow-up test study using a one-factor Complete Random Design (RAL) to determine the effect of subletal dose of LD50-48 hours on the increase in biomass, behavior, and morphology of earthworms (Eudrilus eugeniae). The object of the study is the earthworm (Eudrilus eugeniae) which already has a clitelum with a biomass of 25 grams for each treatment tank. Data analysis was carried out with Proit Analysis to determine the upper threshold, lower threshold, and LD50 value while the analysis of the difference in earthworm biomass from the treatment group was carried out using  the One-Way ANOVA test  at a significance level of 95%. The average treatment was further tested using the DMRT test in the SPSS version 24.0 program. The results showed that: (1) earthworm tolerance to the herbicide 2,4-D dimethyl amine, at the  upper threshold value of 9996.014 ppm, the lower threshold of 3409.972 ppm, the LD50-48 hours of 9015.858 ppm which is practically non-toxic, (2) the response of earthworms (Eudrilus eugeniae) when exposed  to subletal doses of the herbicide 2,4-D dimethyl amine herbicideIt is characterized by a reduced earthworm appetite, a shrinking body shape, and a decrease in biomass.